Brand Naming : The Complete Guide to Creating a Name for Your Company, Product, or Service. - Meyerson, Rob. (New York : Business Expert Press, 2021)
This complete and detailed book, Brand Naming, includes insider anecdotes, tired trends, brand origin stories, and busted myths. Whether you need a great name for a new company or product or just want to learn the secrets of professional word nerds, put down the thesaurus--not to mention Scrabble--and pick up Brand Naming.
Cover -- Halftitle -- Title -- Copyright -- Dedication -- Description -- Contents -- Testimonials -- Foreword -- Acknowledgments -- Introduction -- Part I: Background and Basics -- Chapter 1: How Brand Naming Works -- Chapter 2: Types of Brand Names -- Chapter 3: The Basic Naming Process -- Part II: Hundreds of Ideas -- Chapter 4: The Naming Brief -- Chapter 5: Getting Set Up -- Chapter 6: Basic Name Generation -- Chapter 7: Building Out the List -- Part III: Narrowing Down to One -- Chapter 8: Shortlisting -- Chapter 9: Trademark Prescreening -- Chapter 10: Linguistic Checks -- Chapter 11: What About the Domain? -- Chapter 12: Presenting Names -- Chapter 13: Full Legal and Final Selection -- Chapter 14: Securing and Launching the New Name -- Part IV: Resources -- The Namer's Bookshelf -- The Namer's Browser Bookmarks -- Select Naming Firms (and Related Companies) -- Glossary of Naming Terms -- Naming Brief Template -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books